EP216/#881 Safety and tolerability of olaparib in Indian patients with ovarian cancer: the prospective, single-arm, phase 4 soli trial. (4th December 2022) - Ghosh, Joydeep; Das, Chandan; Gogia, Ajay; Biswas, Ghanashyam; Desai, Chirag; Rajpurohit, Sajjan; Mehta, Prashant; Pavithran, Keechilat; Goswami, Chanchal; Rathnam, Krishna; Limaye, Sewanti; Talwar, Vineet; et al.
Abstract : Objectives: Background: Olaparib is approved as maintenance therapy in patients with platinum-sensitive relapsed (PSR) ovarian cancer (OC). Currently, sparse information is available on the safety of maintenance olaparib in Indian patients Methods: In this prospective, single-arm, multicentre, phase 4 study in India (ClinicalTrials.gov Identifier: NCT04330040 ), eligible females (≥18 years) with PSR OC, in complete response (CR) or partial response (PR) to preceding platinum-based chemotherapy, received olaparib (300 mg BD) for 182 days or until its discontinuation. Patients had post-trial access to olaparib per investigator judgment. Key study endpoints included adverse events (AE), serious AEs and death. Continuous and categorical data were presented as mean (SD) and proportion (%), respectively. Results: Between May 2020 and March 2022, 142 patients were included. The median age was 52.0 years (range 33.0–73.0), mean BMI was 26.1 kg/m 2, 136 (95.8%) had PS of 0, and 122(85.9%) received ≥2 previous cancer therapies. Of 63 patients with known BRCA mutations, BRCA1 mutation was found in 39 (61.9%) patients. CR plus PR plus stable disease (SD) at 24 weeks (clinical benefit rate, CBR) was seen in 73 (53.7%, 95% CI 44.9%-62.3%%) patients. Grade 3+, related, treatment emergent AEs (TEAE) were seen in 51 (37.5%, 95% CI 29.4–46.2%) patients ( table 1 ). Overall, olaparib dose was reduced in 56 (41.2%, 95% CI 32.8–49.9%) patients. Dose discontinuations were reported in 12(8.8%) patients. One patient (0.7%) developed acute myeloid leukemia. Conclusions: SOLI study confirms the safety profile of olaparib in Indian patients with PSR OC. Olaparib was well-tolerated with no new safety concerns